2022
DOI: 10.1002/cmdc.202200484
|View full text |Cite
|
Sign up to set email alerts
|

GluN2A‐Selective NMDA Receptor Antagonists: Mimicking the U‐Shaped Bioactive Conformation of TCN‐201 by a [2.2]Paracyclophane System

Abstract: Under physiological conditions, N‐Methyl‐D‐Aspartate (NMDA) receptors play a crucial role for synaptic plasticity, long‐term potentiation and long‐term depression. However, overactivation of NMDA receptors can result in excitotoxicity, which is associated with various neurological and neurodegenerative diseases. The physiological properties of NMDA receptors are strongly dependent on the GluN2 subunit incorporated into the heterotetrameric NMDA receptor. Therefore, subtype selective NMDA receptor modulators ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Nevertheless, their selectivity at a high concentration (10 uM) was lower than the one observed for TCN-201 since both MPX-004 and MPX-007 inhibited GluN2B current (at 10 uM) by 8% and 30% respectively [113]. TCN-201, a GluN2A NMDAR antagonist, looks more promising as a superior phar macological tool for investigating the roles of GluN2A, since it has higher selectivity for GluN2A compared to GluN2B [113,118], probably because of the interactions at the ligand binding domains (LBDs) of GluN1 and GluN2A subunits. TCN-201′s binding site location is proposed to be at the interface between the LBDs of GluN1 and GluN2A subunits [119] Modulation of LBD interactions has shown promising therapeutic potential.…”
Section: Glun2a and Glun2b Nmda Receptor Antagonistsmentioning
confidence: 95%
See 1 more Smart Citation
“…Nevertheless, their selectivity at a high concentration (10 uM) was lower than the one observed for TCN-201 since both MPX-004 and MPX-007 inhibited GluN2B current (at 10 uM) by 8% and 30% respectively [113]. TCN-201, a GluN2A NMDAR antagonist, looks more promising as a superior phar macological tool for investigating the roles of GluN2A, since it has higher selectivity for GluN2A compared to GluN2B [113,118], probably because of the interactions at the ligand binding domains (LBDs) of GluN1 and GluN2A subunits. TCN-201′s binding site location is proposed to be at the interface between the LBDs of GluN1 and GluN2A subunits [119] Modulation of LBD interactions has shown promising therapeutic potential.…”
Section: Glun2a and Glun2b Nmda Receptor Antagonistsmentioning
confidence: 95%
“…X-ray crystallog raphy results indicated that these compounds bind to a site situated at the interface be tween the GluN1 and GluN2A subunit LBDs [80,123]. TCN-201, a GluN2A NMDAR antagonist, looks more promising as a superior pharmacological tool for investigating the roles of GluN2A, since it has higher selectivity for GluN2A compared to GluN2B [113,118], probably because of the interactions at the ligand binding domains (LBDs) of GluN1 and GluN2A subunits. TCN-201 s binding site location is proposed to be at the interface between the LBDs of GluN1 and GluN2A subunits [119].…”
Section: Glun2a and Glun2b Nmda Receptor Antagonistsmentioning
confidence: 99%